2008
DOI: 10.1103/physreve.77.011914
|View full text |Cite
|
Sign up to set email alerts
|

Detecting directional coupling in the human epileptic brain: Limitations and potential pitfalls

Abstract: We study directional relationships-in the driver-responder sense-in networks of coupled nonlinear oscillators using a phase modeling approach. Specifically, we focus on the identification of drivers in clusters with varying levels of synchrony, mimicking dynamical interactions between the seizure generating region ͑epileptic focus͒ and other brain structures. We demonstrate numerically that such an identification is not always possible in a reliable manner. Using the same analysis techniques as in model system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…In contrast, EEG studies in healthy controls have revealed a front-to-back pattern of directed connectivity, particularly in the alpha band (17)(18)(19)(20)(21)(22), consistent with modeling studies that have shown that such patterns may arise due to differences in the number of anatomical connections (the degree) of anterior and posterior regions (22,23). However, modeled patterns of information flow depend on the assumed strength of the underlying structural connections (22)(23)(24), and the observed EEG patterns strongly depend on the choice of reference (25), which may explain why, controversially, the reverse back-tofront pattern has also been observed in EEG (26)(27)(28). An important advantage of MEG over EEG in this context is that it is referencefree.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, EEG studies in healthy controls have revealed a front-to-back pattern of directed connectivity, particularly in the alpha band (17)(18)(19)(20)(21)(22), consistent with modeling studies that have shown that such patterns may arise due to differences in the number of anatomical connections (the degree) of anterior and posterior regions (22,23). However, modeled patterns of information flow depend on the assumed strength of the underlying structural connections (22)(23)(24), and the observed EEG patterns strongly depend on the choice of reference (25), which may explain why, controversially, the reverse back-tofront pattern has also been observed in EEG (26)(27)(28). An important advantage of MEG over EEG in this context is that it is referencefree.…”
mentioning
confidence: 82%
“…This selective signal-gating mechanism could explain the strong positive correlation between amplitude and dPTE in our study, but it also explains why this correlation is not perfect, as the amplitude of the sending population itself is not the only prerequisite for routing information: There is also the sensitivity of receiving populations. However, given the mesoscopic level at which the analysis was performed and the infancy of this field, future modeling approaches need to include the influence of global structural topology (22)(23)(24) and inhomogeneity of neuronal populations to systematically study how patterns of information flow depend on frequency, power, SNR, and the role of regions within the network. Moreover, experimental studies should investigate if, and how, these patterns of information flow optimize integrative cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic comparison of methods based on phase dynamics and state-space was carried out in [Smirnov & Andrzejak, 2005], where the authors concluded that neither of the methods is better than the other one. Moreover, some spurious dependencies could be identified for real time series analysis [Osterhage et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Among them are approaches based on state-space reconstruction [9][10][11][12][13][14], phases [15][16][17][18][19][20][21], information theory [22][23][24][25][26][27], linear correlation [28][29][30], dynamical Bayesian inferrence analysis [31][32][33][34][35] as well as on neural networks [36,37], among others. A comparison between many of these approaches was done in model systems and also in experimental data [21,35,[38][39][40][41][42]. In this study we apply a state-space approach [14] and a phase-based approach [15,18,19].…”
Section: Introductionmentioning
confidence: 99%